Presence and function of Hbl B', the fourth protein component encoded by the hbl operon in Bacillus cereus. Issue 1 (31st December 2022) - Jessberger, Nadja; Dietrich, Richard; Janowski, Robert; Niessing, Dierk; Märtlbauer, Erwin
ABSTRACT: The genes hblC, hblD and hblA encode the components Hbl L2, L1 and B of the pore forming enterotoxin haemolysin BL of Bacillus cereus . Two variants of the operon existand the more common one additionally contains hblB downstream of hblCDA . Up to now, it was completely unclear whether the corresponding protein, Hbl B', is widely expressed among B. cereus strains and if it has a distinct function. In the present study, it was shown that the hblB gene is indeed expressed and the Hbl B' protein is secreted by nearly all analysed B. cereus strains. For the latter, a detection system was developed based on monoclonal antibody 11A5. Further, a distinct reduction of cytotoxic and haemolytic activity was observed when recombinant (r)Hbl B' was applied simultaneously with L2, L1 and B. This effect was due to direct interaction of rHbl B' with L1. D −6 B. cereus Altogether, we present the first simple tool for the detection of Hbl B' in B. cereus culture supernatants. Moreover, an important regulatory function of Hbl B' in the mechanism of Hbl was determined, which is best described as an additional control of complex formation, balancing the amounts of Hbl B-L1 complexes and the corresponding free subunits.